Scientific Review: Utilization of Market Segmentation in Fish Brain Marketing - Rojak, Abdul; Junianto, Junianto (Fisheries Science Study Program, Faculty of Science and Technology, Muhammadiyah University of Sidenreng Rappang., 2025)
This study aims to review various studies discussing market segmentation strategies for processed fish cakes in Indonesia. The method used is a qualitative descriptive literature study. A total of five relevant scientific journals were analyzed to review the application of market segmentation in the marketing of fish otak-otak in various regions in Indonesia, covering both urban and rural areas, as well as the upper-middle and lower-middle economic market segments. The results of the review show that geographic and demographic segmentation are the most dominant approaches used, both explicitly and implicitly, in identifying consumer groups, while psychographic and behavioral approaches are still limited. The main conclusion of this review is that the success of fish brain marketing is highly dependent on understanding the local market and specific demographics, followed by innovative product adaptation and promotion to meet the preferences and purchasing behavior of modern consumers. These findings can be the basis for MSMEs to design marketing strategies that are adaptive to local market characteristics and adaptive to changes in modern consumer behavior trends.